Ekspose Kemitraan dan Pemberdayaan Ekonomi: Badan Keswadayaan Masyarakat (BKM) Dalam Meningkatkan Kesejahteraan Masyarakat di Kota Bekasi - Imam Haryadi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
This research aim to understand the context of social welfare and community as understand democracy of economic and Ideology that the prosperity of communities Is primary, not the wealth of Individuals and constitute the social rights of people. Appears a problem of agency self- supporting of community, poverty ailevlotion programs undertaken the agency self-supporting of community, and strategies enhancement social welfare undertaken the agency self-supporting community (BKM) Bekasi. Data obtained by Interview (indepth interviews) and Focus Group Discussion to officials of agency self-supporting community In Bekasl covered 45 villages by consideration of agency self-supporting community as a potential in economic development and social welfare of the community, have a planned program, has a standard of unit financial management, having a partner who joined In the Self-Help Groups, organizational structure, legality of laws and completely administration. Data analysis was done by using descriptive statistics, which test primary data using descriptive statistics-qualitative. BKM as poverty alleviation programs and strategies to improve the social welfare of the people be able to increase optimalization the economic potential, braid of partnership and prosperity of empowerment and economic. BKM's program contained in the medium-term work program and annual programs and economic empowerment with BKM, where the strategy mentoring program BKM conducted in partnership with the Bank BRI, Social Worker of Community, PT. Unilever, PT. Hangson, PT. Prlskon, Bank Mandiri, Yayasan Mitra Lestari, Social Security, Bank BTN, BPRS, RS. Rosana Medlka. Strategies undertaken to further empower the community In Improving the economic potential and prosperity by providing training, ciipltal stlmultint and activities that have a economic and soclol urgency to Improve and further empower people toward prosperity